ANALISIS PENGARUH BUDAYA ORGANISASI, WORK-LIFE BALANCE DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. GREEN NATURE INDONESIA - Putri, Chika Adien Aulya; Agustina, Tri Siwi; Ekowati, Dian (PT Naureen Digital Education, 2024)
The company's culture can enhance team members' productivity, related to motivation and a satisfactory level of job satisfaction for employees to perform optimally and maximize opportunities offered by the company. The aim of this study is to investigate and explain how organizational culture, work-life balance, and job satisfaction influence employee performance at PT. Green Nature Indonesia. A quantitative approach was used in this research. Data analysis included tests for data normality, multicollinearity, heteroskedasticity, multiple linear regression, coefficient of determination (R2), simultaneous test (F), and partial test (T). The findings of this study confirm that both partially and collectively, organizational culture and job satisfaction have a significant and positive impact on employee performance at PT. Green Nature Indonesia. However, the balance between work- life and job satisfaction does not have a significant impact on employee performance at PT. Green Nature Indonesia